POLY4:A Multi -Nutrient Fertilizer – Suitability for Organic Farming - BATHULA, SUNITHA; Gopinath, K. A.; Kumari, V. Visha; Ramanjaneyulu, A. V.; Suvana; Yakadri, M. (Chronicle of Bioresource Management, 2023)
Fertilizers are the critical inputs in agriculture and their use is increasing day by day. The need of the hour is therefore, maximizing the production with sustainability. Indiscriminate use of N-based fertilizers led to the deficiency of other macro and micronutrients, greenhouse emissions, soil and water pollution. Now a days, the fertilizers manufactured with low carbon foot print and from natural or mineral sources are gaining popularity. Among many, polyhalite (POLY4) has been identified as a multi-nutrient fertilizer and it is obtained from mineral ore containing polyhalite (K2SO4. MgSO4.2CaSO4.2H2O), which is known to improve yields in different crops. Furthermore, it can also be used as an organic multi-nutrient fertilizer as it is obtained directly from mineral source without any chemical process. However, the information on uses and benefits of polyhalite is meager hence an attempt has been made to compile and synthesize available information for the benefit of all the stake holders.